Engineering rock mechanics an introduction to the principles - Hudson, John (John A.); Harrison, John P. (Tarrytown, N.Y. : Pergamon, 2005)
Engineering rock mechanics is the discipline used to design structures built in rock. These structures encompass building foundations, dams, slopes, shafts, tunnels, caverns, hydroelectric schemes, mines, radioactive waste repositories and geothermal energy projects: in short, any structure built on or in a rock mass. Despite the variety of projects that use rock engineering, the principles remain the same. Engineering Rock Mechanics clearly and systematically explains the key principles behind rock engineering. The book covers the basic rock mechanics principles; how to study the interactions between these principles and a discussion on the fundamentals of excavation and support and the application of these in the design of surface and underground structures. Engineering Rock Mechanics is recommended as an across-the-board source of information for the benefit of anyone involved in rock mechanics and rock engineering.
Preface -- Introduction -- Geological Setting -- Stress -- In situ Stress -- Strain -- Intact Rock -- Discontinuities -- Rock Masses -- Permeability -- Anisotropy and Inhomogeneity -- Testing Techniques -- Rock Mass Classification -- Rock Dynamics and Time Dependent Aspects -- Rock Mechanics Interactions and Rock Engineering Systems (RES) -- Excavation Principles -- Stabilization Principles -- Surface Excavation Instability Mechanisms -- Design and Snalysis of Surface Excavations Underground Excavation Instability Mechanisms Design and Analysis of Underground Excavations References -- Appendices -- Index.
Includes bibliographical references (p. [393]-397) and index.
Keywords: Rock mechanics; Electronic books